DEIXIS ON WEDNESDAY: WHAT ARE THEY? - Yulianingrum, Fauziah; Hawa, Faiza; Affini, Laily Nur (Universitas Muria Kudus, 2023)
This research aims to classify the kinds of deixis and identify the most dominant deixis used in the Wednesday serial movie. It also analyzes to whom, what, and where the actresses are addressed based on the deixis used in the utterances in the Wednesday serial movie. The method used in this research is the descriptive-qualitative method. The researcher applied Levinson’s theory to identify and classify the kinds of deixis in the Wednesday serial movie. The data used in this research are utterances spoken by the main character in the Wednesday serial movie. In analyzing the research, the researcher found 1.805 deictic words included in the kinds of deixis. According to the findings of this research, there are five kinds of deixis contained in the Wednesday serial movie from chapters I -VIII, namely person deixis with a percentage of 83,4%, time deixis with a percentage of 4,4%, place deixis with a percentage of 2,6%, social deixis with a percentage of 4,7%, and discourse deixis with a percentage of 4,9%. The most dominant deixis used in the Wednesday serial movie is person deixis. In general, person deixis shows the person as a speaker, listener, or someone who is addressed in a speech event. Time deixis indicates the time period when an utterance is spoken; place deixis indicates the relative location of participants in a speech event; social deixis indicates the social relationship between the speaker and the listener; and discourse deixis is concerned as if it is used to relate to other parts of the discourse.